GEO-ECONOMIC ANALYSIS OF INDO-PACIFIC ECONOMIC FRAMEWORK (IPEF) STRATEGIES: A STUDY OF SINO-RUSSIAN COOPERATION - Kaur, Arpit; Singh, Urvashi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores the geo-economic dimensions of the Indo-Pacific Economic Cooperation (IPEF) strategies, with a focus on Sino-Russian Cooperation. The IPEF, led by the United States, aims to establish a rules-based economic order in the Indo-Pacific, countering the influence of China and Russia. Through a geopolitical lens, this article analyses how China and Russia leverage economic tools, such as trade, investment and strategic partnerships, to challenge the IPEF and advance their regional interests. It examines the interplay between economic statecraft and geopolitical objectives, highlighting the strategies employed by both nations to project power and secure influence in the Indo-Pacific. The study reveals that Sino-Russian cooperation not only seeks to undermine the U.S. economic initiatives but also promotes an alternative regional order that aligns with their strategic goals.